Measurement of verticality construction of bushings for laboratory construction materials
This contribution describes process which was used for verticality measurement of the bushings for laboratory construction materials in the pavilion of testing. This pavilion is newly built in VŠB-TU Ostrava, Faculty of Civil Engineering, as part of the Testing house of the building materials. The requirement of the building investor was to determine the verticality of the bushings placed between the first aboveground and the first underground floor. After the building finishing, the bushings with the diameter 70 mm will be used for loading tests of various building materials. The final number of bushings is 169, and they are placed lengthwise and crosswise in the step of 750 mm. The centres of the bushings were measured by polar method in pavilion local coordinate system. The precision of the bushing centres determination was